Organizational Intelligence and Employee Performance: The Mediating Role of Distributive Justice - Shabbir, Muhammad Qasim; Khalid, Waleed; Ali, Muhammad Haider (Information Management and Business Review, 2016)
Abstract: A well thriving education system, initiate and promotes innovation along research, is a key to the performance, productivity and sustainability in the august world class universities, colleges and schools. Globalization and digital revolution are creating new strategic competition and advancement as, a result innovative knowledge and learning’s are driving our economic system. Both public and private organizations are forced to adopt these innovative and technical reforms in order to survive in a competitive environment, which can be possible through spiraling education system by research and innovative techniques. This study intends to investigate the mediating effects of distributive justice on relationship between organizational intelligence and employee performance in education sector. Based on a sample of 113 employees and using structural equation modeling approach, the organizational intelligence is found to have positive effects on distributive justice. The findings of the study suggest that the effects of organizational intelligence on employee performance are fully mediated by distributive justice. This study provides a strapping foundation for all educational institutes to analyze whether they are implementing strategic management practices or not. Systematic and assertive implementation of these practices will not only uplift the quality and standards of educational institutions but also essential for better performance of every industry.